The Application Of Small Side Games Training On Passing Techniques And Performance In Futsal Games - Shepia Eka; Kartono Pramdhan; Ricky Ferrari Valentino (Journal of Physical and Outdoor Education, 2026)
This research aims to determine the effect of Small Sided Games (SSG) training on the improvement of passing techniques and performance in futsal games. The passing technique is one of the basic skills that is very important in futsal because it plays a significant role in the effectiveness of team cooperation. This study uses a quantitative approach with an experimental method. The research design used is One Group Pretest-Posttest Design for passing technique, and Posttest-Only Control Group Design for game performance. The sample in this study consists of 15 male futsal club members from STKIP Pasundan Cimahi. The instrument used is a four-sided passing test with a rebound board for passing technique, while game performance is measured using the Game Performance Assessment Instrument (GPAI) scoring format that includes seven indicators and is directly observed in the context of the match. Data analysis was conducted through normality tests, reliability tests, paired sample t-tests, and independent sample t-tests. The results of the study indicate a significant improvement in passing technique after treatment with a significance value of 0.000 (p < 0.05), which indicates that Small Sided Games training is effective in improving passing ability. Additionally, there is a significant difference in game performance scores between the experimental and control groups (p < 0.001), which shows that SSG training also has a positive impact on game performance. Thus, Small Sided Games training has been proven to significantly influence the improvement of passing techniques and futsal performance, and is recommended as an effective alternative training method in the learning and coaching of futsal.